(untitled) (Research, Society and Development, 2021)
The use of plants for medicinal purposes is performed empirically by traditional knowledge with the use of preparations that seek to extract their active principles, and are considered to be fundamental to human health. In this context, the aim of the present study was to of this study was to carry out a systematic review of the biological activities of the Arecaceae family distributed throughout Brazil. This research was carried out through a comprehensive search using the following databases, Scopus, Portal Periódicos Capes, PubMed, Google Scholar and Science Direct, using the following descriptors: “Arecaceae” and “Biological properties of the family Arecaeae”, checked at <www.theplantlist.org/> to check synonyms. It was possible to identify numerous biological activities in the arecaceae family, among the most recurring ones, the antioxidant, antimicrobial and anti-inflammatory activity. These activities are justified by the presence of fatty acids, phenolic compounds, alkaloids and terpenes. Studies routinely report lauric acid as a major in the plants of this family, which makes it a potential compound to cure or assist in the treatment of various diseases.